SHADOW ECONOMY AND CORRUPTION IN THE BALKANS – IS THERE A CONNECTION AND WHAT SHOULD BE DONE - Radostina Ivcheva (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
Economies in the Balkans are lagging behind more advanced countries in Europe in their economic development. In some sense that could be a result of the high share of the shadow economy in those countries. Research points out several causes of shadow activities such as low tax morale, high levels of unemployment, weak business environment and very high poverty levels, lack of trust in the state and the public institutions, high perceptions of corruption and also the high taxation levels. This issue affects directly the economy as well as indirectly the whole society. This paper aims to find a positive link between the volumes of the shadow economy and corruption in eight Balkan economies: Slovenia, Croatia, Bosnia and Herzegovina, Serbia, Montenegro, Kosovo and North Macedonia and Bulgaria.
Keywords: shadow economy, corruption, socio economic issues